The effect of oil-heat treatment on color, chemical and mechanical properties of acacia mangium. - Ros Syazmini Mohd Ghani (2017)
Colour changes, chemical composition and mechanical properties of oil-heat treated, 18 years old, Acacia mangium were investigated. The sapwood and heartwood of Acacia mangium underwent hot oil treatment using crude oil at temperatures of 180oC, 200oC and 220oC for 30, 60 and 90 minutes. The colour changes, chemical compositions and mechanical properties in wood were tested using chroma-meter, TAPPI standard and static bending test, respectively. ANOVA was applied to determine the significant relationship between treatment variables and wood properties. The result showed oil-heat treatment reduced the lightness of the wood and darkened both parts of wood. Holocellulose, α-cellulose, hemicellulose and extractive contents decreased with increasing duration and temperature. The strength of the wood was reduced after oil-heat treatment as a result of α-cellulose and hemicellulose degradations. The relationship between wood properties and treatment variables by ANOVA indicated that temperature is the dominant variable affecting the properties of oil-treated wood. Extractive and Klason lignin influenced the colour properties of oil-treated wood while strength of wood was attributed to the presence of high content of α-Cellulose.